Money illusion and the long-run Phillips curve in staggered wage setting models - Andrea Vaona (Kiel Institute for the World Economy (IfW), 2011)
We consider the effect of money illusion - defined referring to Stevens' ratio estimation function - on the long-run Phillips curve in an otherwise standard New Keynesian model of sticky wages. We show that if households under-perceive real economic variables, negative money non-superneutralities will become more severe. On the contrary, if households over-perceive real variables, positive money nonsuperneutralities will arise. We also provide a welfare analysis of our results and we show that they are robust to the inclusion of varying capital into the model. Firms' (over-)under-perception of the real prices of production inputs strengthens) weakens negative money non-superneutralities. In an appendix, we investigate how money illusion affects the short-run effects of a monetary shock.
Keywords: E3; E20; E40; E50; 330; Phillips curve; inflation; nominal inertia; monetary policy; dynamic general equilibrium; money illusion; Stevens' ratio estimation function; Phillips-Kurve; Geldillusion; Neukeynesianische Makroökonomik; Lohnrigidität; Theorie